Determination of Moisture Content in Thioalcohols by Karl Fischer Coulometry - Yan, Miaomiao; Yu, Min; Guangcheng, Wei (Asian Journal of Chemistry, 2010)
The sulfhydryl group in thioalcohols can very easily react with iodine in Karl-Fischer reagent, so it will change the stoichiometrical ratio of Karl-Fischer reaction, then the results of the determination will be inaccurate. Hence, an indirect method was adopted to mask the active sulfhydryl group and then determined the water content in masked thioalcohols. One kind of masking agent and the reactive condition were selected to mask the thioalcohols experimentally and sought the optimal condition from the obtained data. The recovery is among 100-105 % and the relative standard deviation is less than ± 4 %.